Breach of Tolerance: Primary Biliary Cirrhosis - Wang, Lifeng; Wang, Fu-Sheng; Chang, Christopher; Gershwin, M. Eric (Seminars in Liver Disease, 2014)
In primary biliary cirrhosis (PBC), the breach of tolerance that leads to active disease involves a disruption in several layers of control, including central tolerance, peripheral anergy, a “liver tolerance effect,” and the action of T regulatory cells and their related cytokines. Each of these control mechanisms plays a role in preventing an immune response against self, but all of them act in concert to generate effective protection against autoimmunity without compromising the ability of the host immune system to mount an effective response to pathogens. At the same time, genetic susceptibility, environmental factors, including infection agents and xenobiotics, play important roles in breach of tolerance in the development of PBC.
Keywords: apoptosis; autoreactive T cells; antimitochondrial antibodies; liver-tolerance effect; pyruvate dehydrogenase complex